GABA mechanisms of the nucleus of the solitary tract regulates the cardiovascular and sympathetic effects of moxonidine - Alves, Thales B.; Totola, Leonardo T.; Takakura, Ana C.; Colombari, Eduardo [UNESP]; Moreira, Thiago S. (Elsevier B.V., 2016)
The antihypertensive drugs moxonidine and clonidine are alpha(2)-adrenoceptor and imidazoline (I-1) agonists. Previous results from our laboratory have shown that moxonidine can act in the commissural nucleus of the solitary tract (commNTS). In addition, some studies have shown that GABA or glutamate receptor blockade in the RVLM blunted the hypotension produced by these antihypertensive agents in spontaneously hypertensive rats. Therefore, in the present study we verify whether the cardiovascular and sympathetic effects produced by moxonidine in the commNTS are dependent on GABAergic or glutamatergic mechanisms. Mean arterial pressure (MAP) and splanchnic sympathetic nerve activity (sSNA) were recorded in urethane-anesthetized, and artificially-ventilated male Wistar rats (250-350 g). Injection of the GABAA antagonist bicuculline (25 pmol/50 nL) into the commNTS reduced the hypotension as well as the sympathoinhibition elicited by moxonidine. Prior injection of the glutamate receptor antagonist kynurenic acid (2.5 nmo1/50 nL) into the commNTS was not effective in reducing the hypotension and sympathoinhibition elicited by moxonidine. Therefore, we conclude that the hypotensive and sympathoinhibitory effects elicited by microinjection of moxonidine into the commNTS are dependent on GABA receptors, but not ionotropic glutamate receptors. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Hypertension; Commissural NTS; Sympathetic activity; Moxonidine; GABA